Fiscal Consolidation Plans with Underground Economy - Maria Ferrara; Elisabetta Marzano; Monica Varlese (Center for Economic Studies and ifo Institute (CESifo), 2022)
Fiscal consolidation literature often neglects that there are economies with a sizable underground sector and that most of time it is accounted in GDP statistics. This produces non negligible effects on fiscal multipliers. This paper explores a fiscal consolidation plan calling for a downsizing of the underground sector as well. The analysis refers to the Italian economy that, among European countries, is the second for high public debt and has one of the highest size of tax evasion. Results show that it is possible to both reduce public debt and tax evasion through a temporary cut in public spending associated with a permanent drop in tax rates. In this context a reallocation of resources from the underground to market sector operates.
Keywords: E26; E32; E62; E63; H26; 330; fiscal consolidation plans; underground economy; DSGE modelling